Sensory Study on Persea Americana Durability as Seed-Based Flour Innovation - Syed A Kadir, Syed Shikh; Abdul Rasid Abdul Razzaq; Abdul Rahman, Abdul Wafi; Hairuddin Harun; Mohd Akmal Rohiat; Raden Ismail, Raden Mohd Farhan Helmy; Abd Rahim, Fatin Amirah (Research and Innovation in Technical and Vocational Education and Training, 2021)
The avocado fruit, better known as Persea Americana, is a plant that has many nutrients such as protein, fat, vitamin A carbohydrates including its seeds. This study aimed to develop an avocado seed-based flour innovation product, evaluate based on sensory observations on the durability of avocado seed-based flour product innovation in terms of color, texture, odor and taste and identify suitability for packaging of avocado seed-based flour products. This study took 14 days to get the data to analyze. The study is based on observation and is recorded in a sensory research form that takes into account colors, textures, smells and flavors. As a result of the observations, there were changes in color, odor and taste while no changes in texture were noted. As a result of the research conducted, product development is well underway, and improvements need to be made so that innovative flour products can be marketed in the future.